Differences in Student Mathematics Learning Achievement Based on Parenting Patterns of Parents of Students Class VIII SMP Negeri 3 Wundulako - Rahayu, Deti Sri; Mashuri, Sufri; Diana, Diana; Sari, Dian Ulfa (Universitas Sembilanbelas November Kolaka, 2021)
The purpose of this study was to determine: To determine students' learning achievement in mathematics based on parenting styles of students at SMP Negeri 3 Wundulako and to find out the difference in students' learning achievement in mathematics based on parenting styles at SMP Negeri 3 Wundulako. The population in this study were all students of class VIII SMP Negeri 3 Wundulako, totaling 47 students divided into 2 classes, namely VIII A and VIII. This study uses descriptive quantitative research, where the researchers used descriptive methods with quantitative approaches. The results showed that: Differences in students' learning achievement in mathematics based on parenting styles of class VIII students at SMP Negeri 3 Wundulako.